Analisa Tanggung Jawab Pemerintah Pada Masa New Normal Untuk Memenuhi Hak Pendidikan Masyarakat Akibat Pandemi Covid-19 - Mariana Mugiono (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Abstract: Due to the COVID-19 pandemic, various guidelines have been established to break the chain of transmission of the COVID-19 virus in Indonesia. One of the government's efforts in Indonesia is to urge the public to practice physical distancing. This means maintaining distance between people, staying away from all forms of crowds and group activities, and urging people to avoid demonstrations. People are involved. This effort is aimed at the community to break the chain of the current Covid-19 pandemic outbreak. Education in Indonesia is also one of the areas affected by the Covid-19 pandemic. With restrictions on interaction, the Ministry of National Education has also instructed to close schools and replace the process of education and learning activities (KBM) with the use of an online system. The use of this online learning system can cause various problems faced by students and teachers, such as teachers failing to complete lessons or teachers changing other tasks. Another problem with this online learning system is that education is a human right that must be earned, so while education must remain effective, many restrict access to information. This research is descriptive analytical research, which is research that aims to provide a concrete picture or description of the state of the object or problem under study without drawing general conclusions.be people, institutions, communities and others which are currently based on visible facts or what they are. Keyword: Education, covid-19, online learning, education rights, government Abstrak: Akibat pandemi COVID-19, berbagai upaya penanganan khususnya dalam protokol kesehatan telah ditetapkan untuk memutus mata rantai penularan virus COVID-19 di Indonesia. Salah satu upaya pemerintah di Indonesia adalah menghimbau kepada masyarakat untuk melakukan physical distancing. Artinya, menjaga jarak antarmanusia, menjauhi segala bentuk keramaian dan aktivitas kelompok, serta mengimbau agar menghindari aksi unjuk rasa. Orang-orang terlibat. Upaya tersebut ditujukan kepada masyarakat untuk memutus mata rantai wabah pandemik Covid-19 saat ini. Pendidikan di Indonesia juga menjadi salah satu daerah yang terkena dampak pandemi Covid-19. Dengan pembatasan interaksi, Kemendiknas juga telah menginstruksikan untuk menutup sekolah dan mengganti proses kegiatan pendidikan dan pembelajaran (KBM) dengan penggunaan sistem online. Penggunaan sistem pembelajaran online ini dapat menimbulkan berbagai permasalahan yang dihadapi siswa dan guru, seperti guru gagal menyelesaikan pelajaran atau guru mengganti tugas lainnya. Masalah lain dengan adanya sistem pembelajaran online ini adalah bahwa pendidikan adalah hak asasi manusia yang harus diperoleh, sehingga sementara pendidikan harus tetap efektif, banyak yang membatasi akses informasi. Penelitian ini merupakan penelitian deskriptif analitis, yaitu penelitian yang bertujuan untuk memberikan gambaran atau gambaran yang kongkrit tentang keadaan objek atau masalah yang diteliti tanpa menarik kesimpulan yang bersifat umum. Kata kunci: Pendidikan, covid-19, pembelajaran online, hak pendidikan, pemerintah